2004
DOI: 10.1074/jbc.m401210200
|View full text |Cite
|
Sign up to set email alerts
|

Cation Diffusion Facilitator Proteins Modulate Raf-1 Activity

Abstract: The Ras-extracellular signal-regulated kinase (ERK) cascade is a critical intracellular signaling pathway that regulates growth, survival, and differentiation. Previous work established that Ras-GTP binds to, and facilitates the activation of, the protein kinase Raf-1. Recently, it was demonstrated that the cation diffusion facilitator (CDF) proteins are involved in Ras-ERK signaling by use of a Caenorhabditis elegans genetic screen that identified suppressors of activated Ras. In the current work, we demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
54
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 33 publications
3
54
0
Order By: Relevance
“…A different mechanism for zinc-mediated down-regulation of Raf-1 activity has been found in Xenopus oocytes. In this study, the kinase activity of Raf-1 is promoted by binding to the zinc export protein ZnT-1, and the addition of zinc inhibits the binding of Raf-1 to ZnT-1 (31). Such a mechanism of Raf-1 inhibition by zinc can be excluded in monocytes, because inhibition of sGC (9) or PKA antagonized the inhibitory effect of zinc on TNF-␣ secretion, providing evidence for an involvement of cyclic nucleotide signaling.…”
Section: Discussionmentioning
confidence: 78%
“…A different mechanism for zinc-mediated down-regulation of Raf-1 activity has been found in Xenopus oocytes. In this study, the kinase activity of Raf-1 is promoted by binding to the zinc export protein ZnT-1, and the addition of zinc inhibits the binding of Raf-1 to ZnT-1 (31). Such a mechanism of Raf-1 inhibition by zinc can be excluded in monocytes, because inhibition of sGC (9) or PKA antagonized the inhibitory effect of zinc on TNF-␣ secretion, providing evidence for an involvement of cyclic nucleotide signaling.…”
Section: Discussionmentioning
confidence: 78%
“…These regions may therefore contain the key structural elements that enable the interaction of ZnT-1 with other proteins, including the ␤-subunit. The notion that the underlying mechanism for ZnT-1 activity involves protein-protein interaction has been shown previously in other systems (45,65). Jirakulaporn et al (45) reported that the ZnT-1 C-terminal segment binds to N-Raf (cytoplasmic protein) and by doing so activates the extracellular signal-regulated kinase-mitogen-activated protein kinase cascade (ERK-MAPK).…”
Section: Discussionmentioning
confidence: 99%
“…The notion that the underlying mechanism for ZnT-1 activity involves protein-protein interaction has been shown previously in other systems (45,65). Jirakulaporn et al (45) reported that the ZnT-1 C-terminal segment binds to N-Raf (cytoplasmic protein) and by doing so activates the extracellular signal-regulated kinase-mitogen-activated protein kinase cascade (ERK-MAPK). Moreover, their study also showed that high levels of free zinc impair the interaction between ZnT-1 and Raf-1, which may imply a conformational change of ZnT-1 in the presence of high zinc concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together with our results, this suggests that the cytosolic C-terminal tail of CDF/ZnT proteins is important in determining their oligomeric partner molecules. The cytosolic C-terminal tail of CDF/ZnT proteins has been shown to be important for binding of both zinc and a signal transduction molecule (12,13,37). Further studies may reveal additional functions for the C-terminal region.…”
Section: Discussionmentioning
confidence: 99%